The imperative for culturally specific suicide prevention models beyond the Western gaze - Ruan, Qian-Nan; Qian, Jing; Lin, Xiu-Shuang (Frontiers in Psychiatry, 2026)
Suicide remains a critical global public health challenge, with distinct prevalence patterns and risk factors observed across different cultural contexts. While evidence-based prevention strategies, such as Cognitive Behavioral Therapy (CBT), crisis hotlines, and gatekeeper training, have been developed predominantly in Western settings and have demonstrated efficacy, their application in non-Western populations faces unique cultural hurdles. This perspective article examines the limitations of applying individualistic suicide prevention models without sufficient adaptation to East Asian cultural contexts, which are often characterized by “shame-honor” dynamics and collectivist values. We acknowledge the significant contributions of existing Western frameworks but argue that a reliance on these models, if unexamined, may overlook specific barriers to help-seeking, such as the intense stigma associated with “loss of face” and the perception of mental distress as a burden to the family. By analyzing the “cultural mismatch” between the Western independent self and the East Asian interdependent self, this article calls for a paradigm shift toward “cultural grounding.” We propose that the field must move beyond superficial adaptation toward the co-creation of interventions that integrate indigenous cultural narratives and social structures. This approach aims not to replace existing evidence-based practices but to enhance their relevance and accessibility, ensuring that suicide prevention strategies are truly responsive to the diverse realities of global populations.